Strategic Management of Student Organization: For Discipline Enhancement in Islamic Boarding Schools - Susanti, Try; Chaniago, Fransisko; Ibarra, Florante P; Fitriani, Suci; Ansari, Desi; Hamdan, Hamdan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The purpose of this study is to analyze the strategic management of the student organization in enhancing discipline at Al-Kautsar Integrated Islamic Boarding School, Tebo Regency, Jambi Province. The research method used is qualitative with a descriptive analytical approach, involving in-depth interviews with the organization’s supervisor, the chairman, and documentation related to the organization’s programs. The results indicate that the strategic management of the student organization operates effectively through four main processes: planning, organizing, implementation, and supervision. Planning includes the formulation of vision and mission, disciplinary regulations, sanction guidelines, and a structured activity schedule. Organizing involves establishing the organizational structure, assigning tasks based on students’ interests and competencies, and direct guidance from the organization supervisor. Implementation focuses on habituating disciplined behavior through role modeling, regular briefings, habituation and assignment, as well as motivation provision. Supervision is conducted through direct and indirect monitoring, routine weekly and monthly evaluations, and accountability reporting at the end of the term. The implications of this study suggest that the application of strategic management can consistently improve student discipline, create an orderly and conducive pesantren environment, and serve as a model for student organization governance implementation in other pesantrens across Indonesia.